β-cell-targeted blockage of PD1 and CTLA4 pathways prevents development of autoimmune diabetes and acute allogeneic islets rejection - El Khatib, Moustafa (Gene Ther, 2015)
Protection of beta cells from autoimmune destruction potentially cures type 1 diabetes mellitus (T1D). During antigen presentation, interactions between cytotoxic T-lymphocyte antigen-4 (CTLA4) and B7 molecules, or programmed death 1 (PD1) and its ligand PDL1, negatively regulate immune responses in a non-redundant manner. Here, we employed beta cell-targeted adeno-associated virus serotype 8 (AAV8)-based vectors to over-express an artificial PDL1-CTLA4Ig polyprotein or IL10. Beta cell-targeted expression of PDL1-CTLA4Ig or IL10 preserved beta cell mass and protected NOD mice from T1D development. When NOD mice were treated with vectors at early onset of hyperglycemia, PDL1-CTLA4Ig or IL10 alone failed to normalize the early onset of hyperglycemia. When drug-induced diabetic mice received MHC-matched allo-islets, with or without pretreatment of the PDL1-CTLA4Ig-expressing vector, PDL1-CTLA4Ig-expressing islets were protected from rejection for at least 120 days. Similarly, transplantation of PDL1-CTLA4Ig-expressing MHC-matched islets into mice with established T1D resulted in protection of allo-islets from acute rejection, although islet grafts were eventually rejected. Thus, the present study demonstrates the potent immuno-suppressive effects of beta cell-targeted PDL1-CTLA4Ig overexpression against T1D development and allo-islet rejection. The gene-based simultaneous inhibition of PD1 and CTLA4 pathways provides a unique strategy for immunosuppression-free tissue/organ transplantation, especially in the setting of no established autoimmunity.